Decision Making System in Choosing Poultry Medication at PT.Avindo PBM Web-Based Using Forward Chaining - Zanuar Gunawan; Rudy Arijanto (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2019)
The application of web-based decision making system in poultry medicines selection process using forward chaining by PT. Avindo Perdana Bahtera Mulia aims to promote the medicines and to help poultry stock farmers in knowing which medicines needed to be given to poultry that indicated to be diseased, efficiently and effectively. Livestock farmer can also indentify what kind of disease the stock has and the solution of treating that disease, in this case is getting the medicines that manufactured by PT. Avindo Perdana Bahtera Mulia, quickly and accurately. After conducting research at PT. Avindo Perdana Bahtera Mulia, the marketing process is being left to all veterinarians. Sometimes when customers needed help from veterinary to diagnose the sickness of their poultries, the limited number of the veterinary and poultry specialist make customers can’t do anything but wait for the help in the form of medicines suggestions. These reasons above are why this decision making application was finally made. From this application, we can expect the customers can easily know which medicines is right for their poultries and can also order the medicines right away, this can also increase the sales of poultry medicines manufacturer has. It can be concluded that this application can help to providing informations of poultry diseases and marketing the medicines from manufacturer to customers easily, effectively, and efficiently.